Exploring Sphingolipid Implications in Neurodegeneration - Alessenko, Alice V.; Albi, Elisabetta (Frontiers in Neurology, 2020)
Over the past decade, it was found that relatively simple sphingolipids, such as ceramide, sphingosine, sphingosine-1-phosphate and glucosylceramide play important roles in neuronal functions by regulating rates of neuronal growth and differentiation. Homeostasis of membrane sphingolipids in neurons and myelin is essential to prevent the loss of synaptic plasticity, cell death and neurodegeneration. In our review we summarize data about significant brain cell alterations of sphingolipids in different neurodegenerative diseases such as Alzheimer’s disease, Parkinson disease, Amyotrophic Lateral Sclerosis, Gaucher’s, Farber’s diseases, etc. We reported results obtained in brain tissue from both animals in which diseases were induced and humans in autopsy samples. Moreover, attention was paid on sphingolipids in biofluids, liquor and blood, from patients. In Alzheimer’s disease sphingolipids are involved in the processing and aggregation of β-amyloid and in the transmission of the cytotoxic signal β-amyloid and TNFinduced. Recently, the gangliosides metabolism in transgenic animals and the relationship between blood sphingolipids changes and cognitive impairment in Alzheimer’s disease patients have been intensively studied. Numerous experiments have highlighted the involvement of ceramide and monohexosylceramide metabolism in the pathophysiology of the sporadic forms of Parkinson’s disease. Moreover, gene mutations of the glucocerebrosidase enzyme were considered as responsible for Parkinson’s disease via transition of the monomeric form of α-synuclein to an oligomeric, aggregated toxic form. Disturbances in the metabolism of ceramides were also associated with the appearance of Lewy’s bodies. Changes in sphingolipid metabolism were found as a manifestation of Amyotrophic Lateral Sclerosis, both sporadic and family forms, and affected the rate of disease development. Currently, fingolimod (FTY720), a sphingosine-1-phosphate receptor modulator, is the only drug undergoing clinical trials of phase II safety for the treatment of Amyotrophic Lateral Sclerosis. The use of sphingolipids as new diagnostic markers and as targets for innovative therapeutic strategies in different neurodegenerative disorders has been included.